Crossing through Chueca : lesbian literary culture in queer Madrid - Robbins, Jill, 1962- (Minneapolis : University of Minnesota Press, 2011)
In the past two decades the city of Madrid has been marked by pride, feminism, and globalization--but also by the vestiges of the machismo nurtured during the long years of the Franco dictatorship. "Crossing through Chueca" examines how lesbian literary culture fares in this mix from the end of the countercultural movement la movida madrilena in 1988 until the gay marriage march in 2005. Jill Robbins traverses the various literary spaces of the city associated with queer culture, in particular the gay barrio of Chueca, revealing how it is a product of interrelations--a site crisscros
Preface : marching toward marriage -- A brief history of Chueca and Madrid's Queer space -- Lesbian literary identities in the Madrid book business -- The new safita: Andalusia and the phallic woman in Plumas de España -- Lesbian-themed best-sellers and the politics of acceptance -- Dislocations : identity and communication in Cenicienta en Chueca -- Popular lesbian fiction : romance, literature, and legislation -- Conclusion : toward lesbian visibility.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Spanish fiction -- 20th century -- History and criticism; Spanish fiction -- 21st century -- History and criticism; Lesbianism in literature; Lesbian culture -- Spain; Homosexuality and literature -- Spain; Publishers and publishing -- Spain -- Madrid -- History; Books and reading -- Spain -- Madrid -- History -- 20th century; Books and reading -- Spain -- Madrid -- History -- 21st century; Geographical perception -- Spain -- Madrid; Roman espagnol -- 20e siècle -- Histoire et critique; Roman espagnol -- 21e siècle -- Histoire et critique; Lesbianisme dans la littérature.; Culture lesbienne -- Espagne; Homosexualité et littérature -- Espagne; Livres et lecture -- Espagne -- Madrid -- Histoire -- 20e siècle.; Livres et lecture -- Espagne -- Madrid -- Histoire -- 21e siècle.; Perception géographique -- Espagne -- Madrid; FICTION -- General; LITERARY CRITICISM -- Women Authors; Books and reading; Geographical perception; Homosexuality and literature; Lesbian culture; Lesbianism in literature; Publishers and publishing; Spanish fiction; Spain; Spain -- Madrid; 1900-2099; Criticism, interpretation, etc; History